Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Square Terhadap Kemampuan Matematis Peserta Didik Kelas VIII SMPN 8 Padang - CICI RAHMADANI (Jurnal Edukasi dan Penelitian Matematika, 2020)
A mathematicalucommunication abilitysis asskills that mustbbe own by the student’s . However, based on the result of test thatshave done in SMPN 8 Padang it still low and centered teacher learning. This can be improved by applying the cooperative type Think Pair Square learning model so it make student’s become active in the learning process. The purpose of this researchare to know and describes whether the ability of mathematical communication skill of the student’s of the experimental class is better than the control class by applying to Think Pair Square learning models. This type of this research is a combination of quasy experiment with a static group design research design. Based on the results of the research it can be concluded that the mathematical communication ability of students that learn by think pair square is better than than student’s who learn by conventional learning. Keywords- Mathematical Communication Skiils, think pair square learning’s model